QUANTIZATION OF ELECTRONIC STATES ON METAL-SURFACES - Fauster, Thomas (Applied Physics A: Solids and Surfaces, 1994)
An electron in front of a metal surface experiences an attractive force due to the induced image charge. Band gaps in the band structure can prevent a penetration into the metal along certain directions. The Coulomb-like potential supports bound states in front of the surface which correspond to a hydrogen atom in one dimension. These image states can be measured with high resolution by two-photon photoemission. The adsorption of metals modifies the states. If the electrons can penetrate into the metal, quantum-well states can develop corresponding to standing waves in the overlayer. Image states on small islands show the quantization effects due to the lateral localization. The spectroscopy of image states by two-photon photoemission permits the investigation of growth and morphology of deposited metal layers, a well as the illustration of fundamental quantum-mechanical effects.